On the Move—Considerations on Carmen Francesca Bancius Langgedicht Lebt wohl ihr Geliebten und Genossen (2018) and Jaroslaw Rudiš’s Novel Winterbergs letzte Reise (2019) - Wolting, Stephan (Porównania, 2022)
Using the examples of two works of Central European authors (a female and a male) who write in German as in their „non-native-language“ the article tries to point out attempts to interpretate literary reprensentations of special miogration discourses under the focus oft two extremely opposing current theoretical positions: the „move“ (Khanna 2021) according to which migration as an expectation of normality and sedentary life would be he exception today. On the other hand the „solastalgy“ (Morizont 2019) as the way of „home with no exile“. Both works raise awareness for that in a globalized and increasinly world one´own environment is mutating into something foreign, so that the only oportunity would be to sty on the move.